Qt for Symbian - Fitzek, Frank H.P; Torp, Tony; Mikkonen, Tommi (Wiley, 2010)
"The Qt environment is the new platform to make and build mobile applications. Using Qt, you can develop applications and user interfaces once, and deploy them across many desktop and embedded operating systems without rewriting the source code. This widely known and employed cross platform development tool is newly applied to the Symbian platform and will have a massive impact on Symbian phones for the next decade. Qt for Symbian takes an in-depth look at this cutting-edge programming environment. Step-by-step it explains Qt in an easy to access fashion, using simple examples throughout. Key topics include: installing the developer platform / SDK; explaining the basic Qt environment; the extension of the Qt module; communication; sensors; and simple examples for Qt for Symbian and much more."--Publisher?s description.